Implementasi Rest Api Pada Aplikasi E-Perpus (Studi Kasus: SMA Gama Yogyakarta) - Bukhori, Yanuar Muhammad; Artika, Selfi (UNIVED Press, 2023)
The library information system is a software development application used to monitor transaction processes within a library. These transactions encompass book borrowing and returning. This library information system is capable of handling both the book borrowing and returning processes, as well as managing master data, thereby aiding in the organization of the library's book collection. It also facilitates book searches through a catalog and generates transaction reports. The research process included surveys and interviews with library personnel, revealing that the duration of service for transaction activities and difficulties in book management were the primary challenges faced by the GAMA Yogyakarta High School library. With the implementation of the library information system, it is anticipated that it will assist library staff in their work, enhancing the efficiency and effectiveness of library operations, and expediting the service provided by staff for book borrowing and returning transactions.